Sons of the Gods, Children of Earth : Ideology and Literary Form in Ancient Greece - Rose, Peter W. (Cornell University Press, 2019)
In this ambitious and venturesome book, Peter W. Rose applies the insights of Marxist theory to a number of central Greek literary and philosophical texts ...